The effects of trypanosomosis risk on farmers' livestock portfolios: Evidence from The Gambia - Mugalla, C.; Swallow, B.M.; Kamuanga, M. (OAU/STRC, 1999)
Livestock production is an enterprise undertaken by most farm households in The Gambia. Livestock production is affected, however, by the different levels of trypanosomosis risk that pertain across the country. A study of the effects of trypanosomosis on livestock and crop production was initiated in The Central River Division of the Gambia in 1995 by the International Livestock research Institute (ILRI) in collaboration with the International Trypanotolerance Centre (ITC). The study was guided by four hypotheses: (1) households in the higher trypanosomosis risk areas keep fewer livestock per household; (2) households in the higher trypanosomosis risk areas keep a lower proportion of trypanosusceptible breeds and species of livestock; (3) Fulani households keep more livestock per household than other ethnic groups; and (4) Wollof households keep more horses per household than other ethnic groups.